Program Pelatihan Senam Lansia sebagai Upaya Meningkatkan Kesehatan Lansia di Desa Gedangan Kecamatan Mojowarno Kabupaten Jombang - Diana Novita, Silvia; Qotrunnada, Salsabila; Ainiyah, Zachrotul; Ainurrofiq, Muhammad; Asy'ari (Subservire: Jurnal Pengabdian Masyarakat, 2023)
Elderly exercise is one of several efforts to improve the health of the elderly. Someone who has reached old age will be more at risk of disease because of the decline in body condition both physiologically and psychologically. This elderly exercise has been known to prevent the risk of several diseases that often occur in the elderly such as hipertension, diabetes mellitus and others. The purpose of this study was to see the results and effectiveness of the community service program in the form of elderly gymnastics to reduce the number of high blood pressure or hipertension that often occurs in the elderly, especially in Gedangan Village. The implementation method in this research is to carry out a series of activities ranging from health counseling, then elderly exercise, to checking the elderly's blood pressure after participating in gymnastics. Based on data collected from several elderly posyandu in Gedangan Village after participating in this program, it was concluded that this elderly exercise program can reduce blood pressure numbers from the average elderly who participate in this elderly exercise program. So it can be seen that the elderly gymnastics training program is an effective program in maintaining the health of the elderly in Gedangan Village.